Master's of social work students' research self-efficacy, attitude, and knowledge across the foundation year - Johnson-Holmquist, Helen R., author; Morgan, George, advisor; Buchan, Victoria, advisor; Davies, Tim, committee member; Valentine, Deborah, committee member (Colorado State University. Libraries, 2009)
This study examined foundation year MSW student outcomes with regard to the research curriculum. The researcher sought to understand students' attitudes toward research, research knowledge acquisition, and research self-efficacy. The Research Self-Efficacy (RSE) scale (Holden, Barker, Meenaghan, & Rosenberg, 1999) and a modified Kirk-Rosenblatt Research Inventory (K-RRI) (Kirk & Rosenblatt, 1981) were combined to create the survey instrument. Students enrolled at five schools of social work were recruited in the classroom to complete the survey. A pre-post design allowed students' responses at the beginning and end of the foundation year to be matched (n=75). Data collection for this study spanned the academic year of 2007-2008. Self-report responses were analyzed using both descriptive and inferential statistics. Findings suggest that students' attitudes are favorable toward research. Knowledge of research increased over the foundation year. Students who completed one semester of research coursework were compared with those completing two semesters of research coursework. The group with two semesters of research coursework gained statistically significantly more knowledge than the one semester group. Research self-efficacy increased 24 points, a statistically significant change, suggesting a wide range of student confidence and preparedness. Recommendations for both social work practice and education communities are made based on the findings of this study. Changes to the field of evaluation research and technological advances in the last thirty years have been vast. Both faculty and students may benefit by attempting to set aside bias toward research. It is suggested that social work faculty seek to provide a positive learning environment surrounding the research curriculum. Incorporation of the research curriculum with other curriculum components continues to be of interest. The use of service-learning and the field practicum should continue to be explored as a means of integrating the practice and research curriculum (Williams, 2002). The social work practice community can influence the amount and type of research curriculum a social work programs provide. Finally, another research task force may be in order. There remains a need to determine the content of the research curriculum, how the curriculum is taught, and whether or not, research findings are used by social workers.
Covers not scanned.